Assessment of the knowledge of responsible regarding a diet rich in sucrose (Research, Society and Development, 2022)
Excessive consumption of sugars has been frequent and early in childhood and the intake of sugary foods is one of the main factors of the teeth cavities disease. The excessive offer of sucrose made by the responsible raises doubts as to whether this offer is conscious. The objective of this research is to study whether those responsible are aware of the sugar added in the food provided to their children and the risks that generates to them. For this, a printed questionnaire was applied to the pediatric dentistry patients of the Clinical School from the National Institute of Higher Education and Post-Graduate Padre Gervásio (INAPÓS) responsible. Results: 93% of parents were aware of the amount of sugar contained in Coca-Cola; in relation to Danoninho, 57% did not have this knowledge; 83% of the participants understood that the candy often contains sugar, 64% of them did not have the information of the amount contained in Toddynho; as for the maizestarch biscuit, 86% of the parents did not know that there was so much sugan in the food and 57% of them understood the excess in the juice package. Regarding foods that should be harmful to oral health, 29% opted for Coca-Cola and for candy also, 13% for juice and Toddynho and only 8% believe that wafer and Danoninho show payment. It is concluded that parents do not have full knowledge about the sugar contained in their children's diet and its harm.